2016
DOI: 10.1248/bpb.b15-01035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adjuvant Analgesics on Cerebral Ischemia-Induced Mechanical Allodynia

Abstract: Central post-stroke pain (CPSP), a potential sequela of stroke, is classified as neuropathic pain. Although we recently established a CPSP-like model in mice, the effects of adjuvant analgesics as therapeutic drugs for neuropathic pain in this model are unknown. Hence, the aim of the present study was to assess the usefulness of our model by evaluating the effects of adjuvant analgesics used for treating neuropathic pain in this mouse model of CPSP. Male ddY mice were subjected to 30 min of bilateral carotid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
1
1
2
Order By: Relevance
“…To our knowledge, no previous study measured mechanical sensibility to pressure with EVF test after 2 h of MCAO. These observations were in contradiction with previous works in which a reduced mechanical threshold to pressure was observed after global brain ischemia or focal ischemia of the thalamus, reflecting tactile hypersensibility and/or allodynia in neuropathic pain models ( Matsuura et al, 2016a , b ). Contrary to ART, the EVF test did not reveal mechanical sensibility disorders of the right forepaw.…”
Section: Discussioncontrasting
confidence: 99%
“…To our knowledge, no previous study measured mechanical sensibility to pressure with EVF test after 2 h of MCAO. These observations were in contradiction with previous works in which a reduced mechanical threshold to pressure was observed after global brain ischemia or focal ischemia of the thalamus, reflecting tactile hypersensibility and/or allodynia in neuropathic pain models ( Matsuura et al, 2016a , b ). Contrary to ART, the EVF test did not reveal mechanical sensibility disorders of the right forepaw.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, it has been shown that milnacipran reduces thermal and mechanical allodynia in a rat model of neuropathic pain (chronic constriction injury of the sciatic nerve) (Berrocoso et al, 2011). However, in another model of neuropathic pain in mice (central post-stroke pain model), milnacipran did not affect mechanical allodynia thresholds (Matsuura et al, 2016). Co-administration of milnacipran with tramadol potentiated the antihyperalgesic effect of tramadol (Onal et al, 2007), which used chronic constriction injury model as a model for neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Indometacina no demostró tener un efecto analgésico como coadyuvante en un modelo murino de DCPI 45 . No hay estudios que demuestren su efectividad en humanos.…”
Section: Antiinflamatorios No Esteroideos Y Acetaminofenunclassified
“…Los antiinflamatorios no esteroideos (AINES) no han demostrado efectividad para aliviar el dolor neuropático; de hecho, hay pocos ensayos clínicos que comprueben su eficacia 43,44 . En el caso de DCPI, un estudio en un modelo animal de DCPI demostró que la indometacina no era útil para disminuir la alodinia causada por una oclusión carotídea bilateral, sugiriendo su ineficacia para el tratamiento en DCPI 45 .…”
Section: Ainesunclassified